Hypolipidemic effect of Terminalia arjuna (L.) in experimentally induced hypercholesteremic rats - Patil, Ravindra H.; Prakash, K.; Maheshwari, Vijay Laxminarayan (Acta Biologica Szegediensis, 2011)
The hypolipidemic activity of the 50% ethanol extract of bark of T. arjuna were evaluated in rats. The 50% v/v ethanol bark extract at the dose of 40mg/kg body weight, substantially reduced the plasma total cholesterol, triglycerides and LDL cholesterol while HDL cholesterol increased in experimental group in comparison with hypercholesterolemic animal group. Atherogenic index and liver weight of treated animals also showed significant decrease. A significant increase in the activities of lipoprotein lipase and plasma LCAT enhanced hepatic bile acid synthesis and thereby increased degradation of cholesterol to neutral sterols. Furthermore, the activities of lipogenic enzymes like HMG-CoA reductase, glucose-6-phosphate dehydrogenase and malate dehydrogenase were significantly reduced. The bark extract of Terminalia arjuna has excellent hypolipidemic activity. The effect of the extract seems to be mediated through increased hepatic clearance of cholesterol, down regulation of lipogenic enzymes and inhibition of HMG- CoA reductase.